A Survey on Content Based Video Retrieval (International Journal of Engineering and Computer Science, 2014)
Content based video retrieval has a wide spectrum of promising applications, motivating the interests of the researchers worldwide. This paper represents an overview of the general strategies used in visual content-based video retrieval. It focuses on the different methods for video structure analysis, including shot segmentation, key frame extraction, scene segmentation, feature extraction, video annotation, and video retrieval method. This work helps the upcoming researchers in the field of video retrieval to get the idea about different techniques and methods available for the video retrieval.